LITERASI DAN DIGITALISASI KEUANGAN DI GALERI INVESTASI EDUKASI BEI SMA NEGERI 1 PELAIHARI - Tina Lestari; Nico Kosasih; Melania; Marzuki; Ragiel pangestu (Jurnal Abdi Masyarakat, 2026)
The issue of financial literacy and inclusion in Indonesia remains significant, with Sharia financial literacy still at 39.11% (OJK, 2024), contrasting with the rapid 31.21% annual growth of digital economic transactions (Bank Indonesia, 2025). This community service focuses on enhancing financial and digital literacy among students of SMAN 1 Pelaihari, Tanah Laut, South Kalimantan, through the Galeri Investasi Edukasi BEI. The program aims to bridge the gap between theoretical understanding and practical financial skills in the digital era. The method applied involves four stages: interactive seminars, training on financial concepts and digital investment platforms (E-learning LMS, KOINS Syariah, and RDIS), technology implementation, and mentoring with pre-test and post-test evaluation. Results show a 30% average improvement in financial understanding, increased active GI members from 17 to 50 students, and 70% of participants proficient in using digital investment platforms, fostering sustainable financial literacy and inclusion in schools.